Sire Effects on Carcass of Beef-Cross-Dairy Cattle: A Case Study in New Zealand - Martin N; Schreurs N; Morris S; Lopez-Villalobos N; McDade J; Hickson R (MDPI (Basel, Switzerland), 2021)
There is interest in increasing the carcass value of surplus calves born in the dairy industry that are reared for beef production in New Zealand. This experiment evaluated the carcass of Angus and Hereford sires via progeny testing of beef-cross-dairy offspring grown on hill country pasture. Weight and carcass traits were analyzed from 1015 animals and 1000 carcasses of 73 sires. The mean of the progeny group means was 567 kg for live weight at slaughter, 277 kg for carcass weight, 48.9% for dressing-out, 240.3 cm for carcass length, 73.6 cm2 for eye muscle area, 7.4 mm for rib fat depth, 0.91 for marble score, 3.05 for fat color score, 3.01 for meat color score, and 5.62 for ultimate pH. Sire affected (p < 0.05) carcass size and fat traits, but not fat color, meat color, or ultimate pH (p > 0.05). There was a 46 kg increase in carcass weight between the best and worst sires tested. Carcass fat traits were the most variable among sires. The use of genetically superior beef-breed sires over dairy-breed cows has the potential to increase carcass weights from surplus calves born in the dairy industry, while maintaining adequate fat levels and carcass quality.
Keywords: beef-on-dairy; carcass fat; crossbreeding; dairy-beef; genetics; meat yield; progeny test